HILITE—A tool to investigate interactions of matter and light - Stallkamp, N.; Ringleb, S.; Arndt, B.; Kiffer, M.; Kumar, S.; Morgenroth, T.; Paulus, Gerhard G.; Quint, W.; Stoehlker, Th; Vogel, M. (X-Ray Spectrometry, 2020)
Detailed investigations of laser–ion interactions require well-defined ion targets and detection techniques for high-sensitivity measurements of reaction educts and products. To this end, we have designed and built the High-Intensity Laser-Ion Trap Experiment Penning trap setup, which features various ion-target preparation techniques including selection, cooling, compression, and positioning as well as destructive and non-destructive measurement techniques to determine the number of stored ions for all charge states individually and simultaneously. We have recently performed first commissioning experiments of ion deceleration and dynamic ion capture with highly charged ion bunches from an electron beam ion source. We have characterized our single-pass non-destructive ion counter in detail and were able to determine the ion velocity as well as the number of ions from the signals acquired.
CRIS-Team Scopus Importer:2023-04-20